Congenital intrapericardial diaphragmatic hernia presenting radiologically as massive cardiomegaly - Wilson E Sadoh; Stanley U Okugbo (Wolters Kluwer Medknow Publications, 2013)
Intrapericardial diaphragmatic hernia is uncommon condition in which abdominal content herniate into the pericardium. It is mostly of traumatic origin, sometimes it is congenital. Radiologically, the condition may be suspected when the bowel loops are seen. However, diaphragmatic hernia may simulate acute gastrothorax, pneumotocelles and pneumothorax. The case of a 3-month-old infant with congenital diaphragmatic hernia in whom the bowel loops were not seen on chest radiograph and thus presented as massive cardiomegaly, is presented. The child had a successful surgery and was discharged home.